Competence Factor Production in Chemically Defined Media by Noncompetent Cells of Group H Streptococcus Strain Challis - Leonard, C. Gomez (1970)
Chemically defined media for competence factor (CF) production by group H Streptococcus strain Challis-6 are described. CF is produced by noncompetent cells in a glutamate-free medium in which the cells cannot attain competence and by cells prior to their competence development in a glutamate-containing medium. Glutamate was required for competence development, but was not necessary for growth or CF production. Exacting cultural conditions required for the consistent production of relatively high amounts of CF in defined medium and for its recovery are detailed. The most important requirements include the selection of isolates (like Challis-6) which grew well in another defined medium, early harvest of CF because of its demonstrated instability on continued incubation in defined medium, incubation at 37 C, and the addition of glucose. The CF production was more rapid with increasing inocula and with reduced aeration. Aspartate, cystine, and NaCl were not required. Under the conditions described, large amounts of CF were consistently obtained in the culture filtrates of Challis-6 as measured by the induction of competence in strain Wicky cells and their subsequent transformation at frequencies of 6% or greater.